2000
DOI: 10.4049/jimmunol.164.9.4465
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of CD28 and CD40 Ligand in T Cell Activation and Tolerance

Abstract: Costimulation of T cell activation involves both the B7:CD28 as well as the CD40 ligand (CD40L):CD40 pathway. To determine the importance of these pathways to in vitro and in vivo T cell activation, a direct comparison was made of the responses of TCR transgenic T cells lacking either CD28 or CD40L. In vitro, CD28−/− T cells showed a greater reduction in proliferative responses to Ag than did CD40L−/− T cells. The absence of CD28 resulted in defective Th2 responses, whereas CD40L−/− T cells were defective in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
107
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 28 publications
16
107
3
1
Order By: Relevance
“…The addition of canarypox expressing CD40L had not only increased specific CD8 + T cell responses qualitatively but also improved the quality of CD8 + T cells as exhibited by more specific polyfunctional CD8 + T cells and potentially more long lived memory CD8 + T cells as determined by IL-7Rα staining. Some previous reports suggested that CD40L is also important for enhancing CD4 + T cell responses [56][57][58]. Our data are consistent with these reports in that the CD40L regimens enhanced splenocyte proliferation and Th1 cytokine production to vaccine antigens, however, only when CD40L was expressed as a membrane molecule in canarypox vector.…”
Section: Discussionsupporting
confidence: 92%
“…The addition of canarypox expressing CD40L had not only increased specific CD8 + T cell responses qualitatively but also improved the quality of CD8 + T cells as exhibited by more specific polyfunctional CD8 + T cells and potentially more long lived memory CD8 + T cells as determined by IL-7Rα staining. Some previous reports suggested that CD40L is also important for enhancing CD4 + T cell responses [56][57][58]. Our data are consistent with these reports in that the CD40L regimens enhanced splenocyte proliferation and Th1 cytokine production to vaccine antigens, however, only when CD40L was expressed as a membrane molecule in canarypox vector.…”
Section: Discussionsupporting
confidence: 92%
“…non-pathogenic) response in CD154 -/-mice. A recent report has shown that CD154 -/-TCR-transgenic T cells can initially expand, but cannot sustain a Th1 response [24]. We show here that CD154 -/-mice mount a strong Th2 response under conditions that promote a Th1 response in CD154-sufficient mice (CFA normally drives a Th1 response in most experimental systems [25]).…”
Section: Resultsmentioning
confidence: 55%
“…The CD40-CD154 interaction in tolerance induction is controversial with previous studies suggesting that CD154 either was, or was not required [24,27]. To investigate this in our system, we switched from using pMOG to the OVA(323-339) peptide (pOVA), because in later experiments we used OT-II transgenic T cells [22], expressing a TCR that reacts with this peptide in association with I-A b .…”
Section: Cd40-cd154 Signalling Is Not Required For the Induction Of Tmentioning
confidence: 99%
“…Previous studies have demonstrated that CD28 costimulation is required for initiating and sustaining T-cell clonal expansion and differentiation in response to antigen recognition (21)(22)(23)(24)(25). Furthermore, CD28-B7 costimulatory blockade has been shown to inhibit clonal expansion (26) and effector cell differentiation in vivo (27).…”
Section: Effect Of Cd28-b7 Costimulatory Blockade On Alloantigen-specmentioning
confidence: 99%